IMPLEMENTASI STRATEGI DISCOVERY LEARNING PADA MATA PELAJARAN AL-QUR'AN HADIS KELAS XII SAINS A6 MAN 1 KOTA MEDAN - Nayla Fairuz; Tia Nazriah; Latifahul Fitri; Arlina (STKIP Subang, 2025)
This review aims to describe the implementation of the Discovery Learningl, earning strategy in the Al-Qur’an Hadith subject in class IX Science A6 Madrasah Aliyah Negeri 1 Medan, and analyze its impact on the level of activity, motivation, and understanding of students. This study uses a qualitative approach with ap henomenological research type. Data collection techniques are carried outt hrough direct observation of the learning process in the classroom, interviews with Al-Qur’an Hadith subject teachers and students, and reviews of relevant learning documents. Data validity is strengthened through the application of extended participation techniques, observation persistence, negative case analysis, and triangulation of sources and techniques. The results of the study indicate that the implementation of the Discovery Learning strategy has a positive influence on the learning process. Students show increased activity, enthusiasm, and involvement in learning activities, such as group discussions, question and answer activities, and presentations of findings and critical thinking in problem solving. The learning process becomes more meaningful because students are directly involved in discovering material concepts about environmental damage in Raja Empat and analyzing information about the material. The Discovery Learning strategy also contributes to increasing students’ learning motivation and critical thinking skills. Although there are still obstacles in the form of power outages and suboptimal networks, in general the implementation of the Discovery Learning strategy is ablet o create an active, collaborative learning atmosphere between teachers andstudents.